Identification of emission-line stars in transition phase from pre-main sequence to main sequence. Issue 3 (23rd August 2021) - Bhattacharyya, Suman; Mathew, Blesson; Banerjee, Gourav; Anusha, R; Paul, K T; Kartha, Sreeja S
ABSTRACT: Pre-main-sequence (PMS) stars evolve into main-sequence (MS) phase over a period of time. Interestingly, we found a scarcity of studies in existing literature that examine and attempt to better understand the stars in PMS to MS transition phase. The purpose of this study is to detect such rare stars, which we named as 'transition phase' (TP) candidates – stars evolving from the PMS to the MS phase. We identified 98 TP candidates using photometric analysis of a sample of 2167 classical Be (CBe) and 225 Herbig Ae/Be (HAeBe) stars. This identification is done by analysing the near- and mid-infrared excess and their location in the optical colour–magnitude diagram. The age and mass of 58 of these TP candidates are determined to be between 0.1–5 Myr and 2–10.5 M⊙, respectively. The TP candidates are found to possess rotational velocity and colour excess values in between CBe and HAeBe stars, which is reconfirmed by generating a set of synthetic samples using the machine learning approach.